Arquivo do Tribunal Regional do Trabalho a Oitava Região: estudo de caso sobre o processo para destinação de autos judiciais físicos - REAL, Benedito Socorro de Moraes Vila (2021)
This research described the steps taken in the process of assigning physical (paperbased) writs constituents of the Accumulated Documentary Mass (MDA) by the Regional Labor Court of the Eighth Region (TRT8) from 1971 to 1995, from 12 Local Labor Stations at the Headquarters of TRT8, evaluating if the process was carried out in accordance with the instruments in the specific matter for the Labor Judiciary. The destination of documents in the Labor Court comprises an integral part of the document management procedures. The importance of an appropriate allocation plan is therefore evidenced both to avoid accumulation of cumulative documentary mass and to ensure the formation of a permanent collection more representative of the documentation produced. The case study was used as a research strategy. It was operated through applied research, bibliography and participant observation. Data collection was carried out in loco through the participation and observation of the activities carried out in the process of destination of physical judicial records produced by the Regional Labor Court of the Eighth Region. In analyzing the process for the allocation of physical judicial decisions in TRT8, it was verified that this institution practically followed in its totality the instruments in the documentary management of the National Program of Documentary Management and Memory of the Judicial Power (PRONAME), as well as the indispensable steps for the allocation of physical judicial records based on the identification of the instruments and procedures required in each phase, according to PRONAME.